2014
DOI: 10.2337/dc14-2143
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Profile of Intrahepatic Cholestasis of Pregnancy Is Associated With Impaired Glucose Tolerance, Dyslipidemia, and Increased Fetal Growth

Abstract: OBJECTIVEQuantification of changes in glucose and lipid concentrations in women with intrahepatic cholestasis of pregnancy (ICP) and uncomplicated pregnancy and study of their influence on fetal growth. RESEARCH DESIGN AND METHODSA prospective study comparing metabolic outcomes in cholestastic and uncomplicated singleton pregnancies was undertaken at two university hospitals in the U.K. and U.S. from 2011-2014. A total of 26 women with ICP and 27 control pregnancies with no prior history of gestational diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 45 publications
3
110
0
3
Order By: Relevance
“…It is suggested that during gestation if the homeostasis of one mentioned substances is dysregulated it might correlate with higher risk of abnormal levels of another. One of the prospective study of 31 patients with ICP reported a significantly higher blood glucose level while oral glucose tolerance testing (OGTT) [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that during gestation if the homeostasis of one mentioned substances is dysregulated it might correlate with higher risk of abnormal levels of another. One of the prospective study of 31 patients with ICP reported a significantly higher blood glucose level while oral glucose tolerance testing (OGTT) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies in late pregnant rats have demonstrated increased mRNA expression and activity of hormone-sensitive lipase in white adipose tissue [8]. Additionally, it has been shown that the levels and the activity of adipose tissue LPL are reduced in women and rats with late pregnancy [9], thereby decreasing the deposit of lipids in maternal adipocytes.…”
Section: Catabolic Phasementioning
confidence: 99%
“…The drug ursodeoxycholic acid (UDCA) improves itch severity and alters the composition of the serum bile acid pool in ICP 8,9 . Previous studies have suggested that UDCA may be of additional benefit for women with ICP, for example by normalising the ICP-related fall in glucagon-like peptide 1 (GLP1) release following a meal 6 . Indeed, murine studies have demonstrated that UDCA treatment can lower blood glucose concentrations in mice fed a high-fat diet 10 .…”
mentioning
confidence: 99%